PENGARUH MOTIVASI, IKLIM ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (STUDI PADA KOPERASI ASADANA SEMESTA, DENPASAR) - I Made Purba Astakoni (Forum Manajemen STIMI Handayani Denpasar, 2015)
The purpose of this study was to investigate the effect of work motivation,organizational climate and leadership style on employee performance. The researchdata of 162 employees is given by using a questionnaire to take the whole of thepopulation is called the census. In accordance with the above purpose in thisstudy was formulated three hypotheses, among others: motivation positive effecton employee performance, organizational climate positive influence on employeeperformance, and leadership style has positive influence on employee performance.After the questionnaires collected, testing techniques of data is done throughmultiple regression analysis model with the help of Amos program. The resultsshowed Motivation provide a positive and significant effect on the performanceof employees, which means it is stated that hipotesis1 stating that high motivationwill be able to improve employee performance tested at the Cooperative AsadanaSemesta Denpasar. Climate Organization negative effect and no significant effect onthe performance of employees, which means it is stated that hipotesis2 stating thata good organizational climate have not been able to improve the performance ofemployees in the Cooperative Asadana Semesta Denpasar. Leadership style gives anegative effect and no significant effect on the performance of employees, which meansit is stated that hipotesis3 stating that a good leadership style has not been able toimprove the performance of employees in the Cooperative Asadana Semesta Denpasar